2021
DOI: 10.1530/eje-21-0048
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter on use of functional imaging by 11C-metomidate PET for primary aldosteronism subtyping

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, more than half of the patients exhibited discordant results between MTO PET and AVS, which was also observed in our study. Third, although Soinio et al 35 have stated that the tracer activity plateaus at 10 minutes, Crimi et al 36 reported that the optimal start of acquisition is 35 minutes instead of 15 minutes after the tracer injection. We observed similar MTO kinetics reported by Burton et al 21 and O'Shea et al 22 …”
Section: Discussionmentioning
confidence: 98%
“…However, more than half of the patients exhibited discordant results between MTO PET and AVS, which was also observed in our study. Third, although Soinio et al 35 have stated that the tracer activity plateaus at 10 minutes, Crimi et al 36 reported that the optimal start of acquisition is 35 minutes instead of 15 minutes after the tracer injection. We observed similar MTO kinetics reported by Burton et al 21 and O'Shea et al 22 …”
Section: Discussionmentioning
confidence: 98%
“…Although CYP11B1 activity is suppressed by dexamethasone pretreatment, the effect of dexamethasone on CYP11B2 activity, 11 C‐MTO uptake, and lateralization of aldosterone secretion through inhibition of ACTH secretion remains unknown. However, more than 50% suppression of plasma aldosterone concentration has been demonstrated after dexamethasone pretreatment in both APA and bilateral hyperplasia 21,32,33 . The main problem with the 11 C‐MTO isotope tracer is its selectivity for both CYP11B1 and CYP11B2, which is an obstacle for non‐invasive subtype diagnostics in PA, and more specific tracers are awaited 34 …”
Section: Discussionmentioning
confidence: 99%
“…However, more than 50% suppression of plasma aldosterone concentration has been demonstrated after dexamethasone pretreatment in both APA and bilateral hyperplasia. 21,32,33 The main problem with the 11 C-MTO isotope tracer is its selectivity for both CYP11B1 and CYP11B2, which is an obstacle for non-invasive subtype diagnostics in PA, and more specific tracers are awaited. 34 The strength of the current approach is ascertainment of the diagnosis by including only those undergoing surgical treatment and by using immunohistochemistry in addition to assessing postoperative cure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation